Interrogating the configurational stability of atropisomers - Heeb, J-P; Clayden, J; Smith, MD; Armstrong, RJ (Springer Nature, 2023)
Atropisomers are molecules whose stereogenicity arises from restricted rotation about a single bond. They are of current importance because of their applications in catalysis, medicine and materials science. The defining feature of atropisomeric molecules is that their stereoisomers are related to one another by bond rotation: as a result, evaluating their configurational stability (i.e., the rate at which their stereoisomers interconvert) is central to any work in this area. Important atropisomeric scaffolds include C–C linked biaryls, such as the ligand BINAP and the drug vancomycin, and C–N linked amine derivatives such as the drug telenzepine. This article focuses on the three most widely used experimental methods that are available to measure the rate of racemization in atropisomers, namely: (i) kinetic analysis of the racemization of an enantioenriched sample, (ii) dynamic HPLC and (iii) variable-temperature NMR. For each technique, an explanation of the theory is set out, followed by a detailed experimental procedure. A discussion is also included of which technique to try when confronted with a new molecular structure whose properties are not yet known. None of the three procedures require complex experimental techniques, and all can be performed by using standard analytical equipment (NMR and HPLC). The time taken to determine a racemization rate depends on which experimental method is required, but for a new compound it is generally possible to measure a racemization rate in <1 d.